1996
DOI: 10.1007/bf01806154
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the quality of life among long-term survivors of breast cancer

Abstract: breast cancer survivors experienced long-term changes after completion of treatment which affected overall quality of life. However, many positive benefits were also gained which helped to balance the worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(127 citation statements)
references
References 29 publications
5
117
0
5
Order By: Relevance
“…Dow et al (26) and Holzner et al (15) have also reported long-lasting impairments to social support and sexuality in this group of patients.…”
Section: Discussionmentioning
confidence: 52%
“…Dow et al (26) and Holzner et al (15) have also reported long-lasting impairments to social support and sexuality in this group of patients.…”
Section: Discussionmentioning
confidence: 52%
“…Given this finding, it can be argued that attention should be paid to the patients not only during their hospital stay and when they are receiving chemotherapy, but also after disease remission and completion of therapy. [47][48][49] For long-term aftercare, this means that patients should be screened for fatigue regularly, ideally by clinical interview, supplemented with short questionnaires such as the MFI-General Fatigue subscale.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described long-term impairment of QoL, impaired functioning, and continuing symptoms [42,43], as well as a high percentage of distress in breast cancer survivors [16,35], whereas others have reported an improving QoL over time [21,44]. Arndt et al [43] compared breast cancer patients with reference data from the general population.…”
Section: Change Of Qolmentioning
confidence: 99%